Thomas Anstey Guthrie's Madhouse Shuffle: Steps toward a nightmare scenario. Issue 2 (November 2015) - Merchant, Peter
This essay explores a film scenario called An Evil Spirit which Thomas Anstey Guthrie wrote in 1916. It studies the scenario's origins in two remarkable prose narratives, one of them unpublished even now, that Anstey had produced years before: ' The Statement of V. M. patient at Bethnal House Asylum, July: 19: 1886' (1888) and The Statement of Stella Maberly (1896). With the birth of the movies came an opportunity for Anstey to rethink this material, introducing new elements but also drawing out what was latent or implicit in the earlier works. While Anstey was by no means the most technically adept or inventive of screenwriters, he proved an eager learner; and, as a prime beneficiary of the developing early C20 synergy between fiction and cinema, he is a figure from whom we too have much to learn about the spirit of the age.